MANAJEMEN ELECTRONIC GOVERNMENT DI KABUPATEN SEMARANG - Nadila Olivia Intan Putri; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Electronic Government is an effort to organize electronic-based government by utilizing the development of technology and information in order to improve the quality of public services effectively and efficiently. Semarang regency is one of the districts in Indonesia that implement Electronic Government in running its government affairs. The purpose of this study is to know how the Electronic Government management process, as well as the driving factors and inhibiting factors in applying Electronic Government in Semarang regency. The method used in this research is descriptive-qualitative method. The results showed that the management of Electronic Government in Semarang Regency is in the first stage, that is preparation. This condition can be seen from the planning, organizing, directing and controlling in the Office of Communications and Informatics Semarang regency that has not been optimal. This is indicated by the planning process that is still experiencing difficulties in the preparation of the master plan, insufficient human resources, the lack of optimal leadership, budget and infrastructure.